Halal Tourism Branding Strategy: A Study on the Collaboration of Government, Nahdlatul Ulama and Muhammadiyah in Indonesia - Dinta Kharisma Almeira; Aydil Safitri; Surwandono (DINIKA : Academic Journal of Islamic Studies, 2023)
Halal tourism is currently a sector that has become a global trend. As a country with the largest Muslim population in the world, Indonesia should be able to compete in the international arena to form an image as the best country in the halal tourism sector. The article explains the nation branding strategy of the government and Islamic organizations, namely Muhammadiyah and Nahdlatul Ulama, in the hope of being able to raise the halal tourism industry in Indonesia. This research is analytical descriptive research using qualitative methods. The data collection techniques used are literature studies and official websites to process data related to nation branding strategies carried out. The results of this study show the strategies of the government, Nahdlatul Ulama, and Muhammadiyah through three sectors, namely food, hotels, and halal destinations. Of the three sectors, it was found that the government is the actor who has the most effort in improving Indonesia's nation branding through the official website, followed by Nahdlatul Ulama and finally Muhammadiyah. This method is done in order to improve Indonesia's nation branding as a halal tourism country known to the world. This article contributes to the discussion of the potential development of halal tourism in Indonesia.